Academic Journal Retractions and the COVID-19 Pandemic - Caleb Anderson; Kenneth Nugent; Christopher Peterson (SAGE Publishing, 2021)
The 2020 COVID-19 pandemic has produced an unprecedented amount of scientific research, with over 100,000 articles on the SARS-COV2 virus or the associated pandemic published within the first year. To effectively disseminate such a large volume of research, some academic journal publishers altered their review criteria, and many articles were made available before undergoing a traditional review process. However, with this rapid influx of information, multiple COVID-19 articles have been retracted or withdrawn. Some researchers have expressed concern that these retractions call into question the validity of an expedited review process and the overall quality of the larger body of COVID-19 research. We examined 68 removed articles and determined that many of the articles were removed for unknown reasons (n = 22) or as duplications (n = 12); 24 papers were retracted for more significant reasons (data integrity, plagiarism, reporting or analysis, and IRB or privacy issues). The majority of removed papers were from the USA (n = 23) and China (n = 19).